An anti-windup design with local sector and H2/H∞ optimization for flight environment simulation system - Liu, Jiashuai; Wang, Xi; Liu, Xi; Pei, Xitong; Dan, Zhihong; Zhang, Song; Yang, Shubo; Zhang, Louyue (Aerospace science and technology, 2022)
Flight Environment Simulation System (FESS) is an important ground test facility, which can simulate the flight environment to test the performance of the aircraft engine. Focusing on the anti-windup control of FESS in the presence of actuator (magnitude and rate) saturations, an anti-windup design method with local sector and H2/H∞ optimization is proposed. Firstly, the saturation-type static nonlinearities are separated from the dynamic nonlinear model of the actuator, and then an anti-windup architecture with static compensator is constructed. Subsequently, the integrated H2 performance and H∞ performance are used to deal with the saturation nonlinearities to reduce the system performance degradation caused by the magnitude and rate saturations. Meanwhile, the internal stability of the closed-loop system is guaranteed via local sector condition. Finally, an optimization problem based on Linear Matrix Inequalities (LMI) is developed for anti-windup design, in which internal stability, H2 performance and H∞ performance are considered. The designed anti-windup controller is applied to FESS, and the numerical simulation results verify the effectiveness of the proposed method. Furthermore, some key issues in anti-windup design are discussed.